2021
DOI: 10.3389/fcimb.2021.633440
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Protects Against Clostridium perfringens Infection in Mice

Abstract: Toll-like receptor 4 (TLR4) has been reported to protect against Gram-negative bacteria by acting as a pathogen recognition receptor that senses mainly lipopolysaccharide (LPS) from Gram-negative bacteria. However, the role of TLR4 in Gram-positive bacterial infection is less well understood. Clostridium perfringens type A is a Gram-positive bacterium that causes gas gangrene characterized by severe myonecrosis. It was previously demonstrated that C. perfringens θ-toxin is a TLR4 agonist, but the role of TLR4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“… Guo et al (2015) already observed that PGN treatment did not significantly affect TLR2 expression in chicken intestinal epithelial cells. Recently, Takehara et al (2021) speculated that CPA and PFOA could activate the TLR4 on intestinal cells. This result was observed also in this study by the qPCR expression of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“… Guo et al (2015) already observed that PGN treatment did not significantly affect TLR2 expression in chicken intestinal epithelial cells. Recently, Takehara et al (2021) speculated that CPA and PFOA could activate the TLR4 on intestinal cells. This result was observed also in this study by the qPCR expression of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…Docking was performed against TLR1/TLR2 and TLR4/MD2, as they have been widely reported to be important in the innate defense against C. perfringens infection in chickens and mice ( 136 ), although little is known in humans. The lipopeptide and lipopolysaccharide binding sites of TLR1/TLR2 and TLR4/MD-2, respectively, have been structurally characterized ( 137 , 138 ).…”
Section: Discussionmentioning
confidence: 99%
“…perfringens, TLR2 and TLR4 were implicated in sensing C. perfringens and were beneficial to the host . Previously, we also provided evidence demonstrating that mixed lineage kinase-like protein (MLKL) contributes to host protection against C.…”
Section: Introductionmentioning
confidence: 89%
“…Concerning C. perfringens, TLR2 and TLR4 were implicated in sensing C. perfringens and were beneficial to the host. 5 Previously, we also provided evidence demonstrating that mixed lineage kinaselike protein (MLKL) contributes to host protection against C. perfringens invasion via facilitating NLRP3 inflammasomeextracellular traps axis. 6 Therefore, it is not surprising that exploring the innate immunity mechanisms of host combat against C. perfringens will be conducive to the development of new strategies for the effective control of C. perfringens infection.…”
Section: ■ Introductionmentioning
confidence: 98%